ENHANCING FINANCIAL INCLUSION THROUGH MOBILE BANKING SERVICES: THE CASE OF UZBEKISTAN (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article explores the role of mobile banking services in enhancing financial inclusion in Uzbekistan. It analyzes how the rapid development of digital technologies and the increasing availability of mobile devices have contributed to expanding access to financial services, especially among underserved and remote populations. The paper highlights government initiatives, policy reforms, and the activities of commercial banks in promoting digital financial services